2020
DOI: 10.1002/nbm.4318
|View full text |Cite
|
Sign up to set email alerts
|

Fast multicomponent 3D‐Trelaxometry

Abstract: NMR relaxometry can provide information about the relaxation of the magnetization in different tissues, increasing our understanding of molecular dynamics and biochemical composition in biological systems. In general, tissues have complex and heterogeneous structures composed of multiple pools. As a result, bulk magnetization returns to its original state with different relaxation times, in a multicomponent relaxation. Recovering the distribution of relaxation times in each voxel is a difficult inverse problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 132 publications
(266 reference statements)
0
2
0
Order By: Relevance
“…Almeida-Martins et al, Reymbaut et al, and Martin et al increased the dimensionality to 5D and 6D correlation MRI, by additionally varying the shape of b-tensors to encode diffusion and solving the inverse problem with a Monte Carlo-inversion [ 1 , 41 , 51 ]. Zibetti et al jointly solved image reconstruction and multi-component relaxometry, leveraging sparsity and spatial correlation [ 66 ]. Avram et al used voxel-wise optimized L2 regularization for T1-D correlation in vivo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almeida-Martins et al, Reymbaut et al, and Martin et al increased the dimensionality to 5D and 6D correlation MRI, by additionally varying the shape of b-tensors to encode diffusion and solving the inverse problem with a Monte Carlo-inversion [ 1 , 41 , 51 ]. Zibetti et al jointly solved image reconstruction and multi-component relaxometry, leveraging sparsity and spatial correlation [ 66 ]. Avram et al used voxel-wise optimized L2 regularization for T1-D correlation in vivo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, mono-exponential T 1ρ is a macro measurement of an extremely complex microenvironment in the ECM of the muscle. A number of studies have suggested that bi-exponential T 1ρ mapping may better represent the diverse microenvironment that gives rise to the relaxation times in tissue types such as cartilage 23 25 , brain 26 , 27 , liver 28 as well as skeletal muscle 29 . There have been no studies on the application of multi-exponential T 1ρ mapping for the measurement of the muscle microenvironment in muscle stiffness.…”
Section: Introductionmentioning
confidence: 99%